Disorder vs Behavior : The Influence of Internet Gaming Disorder on Phubbing Behavior - Kamila Dwi Mustika Pratiwi; Yuda Syahputra; Lira Erwinda; Nurul Fajri; Melina Lestari (Asosiasi Asesmen Pendidikan (AAP), 2025)
Background of study : This study aims to examine the influence of Internet Gaming Disorder (IGD) on phubbing behavior among students at SMK Ksatrya Jakarta and its implications for guidance and counseling (BK) services. The research employed a quantitative descriptive method with a total sampling technique involving 93 students from grades X and XI. Data were collected using validated and reliability questionnaires and analyzed using simple linear regression via SPSS 20.0. The results revealed a significant influence of IGD on phubbing behavior, indicated by a significance value of 0.000 (< 0.05). Thus, IGD contributes to increased phubbing behavior. The R.Square value obtained was 0.614, which means that the Internet Gaming Disorder variable has an influence of 61.4% on the Phubbing behavior variable. These findings highlight the need for proactive BK interventions to mitigate excessive gaming and improve students' communication.